The Characteristics of Badminton-Related Pain in Pre-Adolescent and Adolescent Badminton Players - Xiao Zhou; Kazuhiro Imai; Zhuo Chen; Xiaoxuan Liu; Eiji Watanabe; Hongtao Zeng (MDPI AG, 2023)
Body pain, often considered as an early sign of injury in young players, warrants thorough study. This study aimed to examine the distribution of badminton-related pain and prevalence in pre-adolescent and adolescent badminton players. Profiles of badminton-related pain were surveyed using a questionnaire among 366 pre-adolescent and adolescent badminton players aged 7-12 years. The distribution of badminton-related pain was described, and the pain incidence was calculated. Proportions of pain per 1000-training-hour exposures were the main outcome measures. The analysis considered various age groups (7-8, 9-10, and 11-12 years) and years of badminton experience (≤2, 2-3, and > 3 years). In total, 554 cases of badminton-related pain were reported. The ankle was the most common site, followed by knee, plantar, shoulder, and lower back. The overall pain rate per 1000-training-hour exposure was 3.06. The 11-12-year-old group showed the highest pain rate, significantly greater than the 7-8-year-old group and the 9-10-year-old group. Additionally, the prevalence of pain exhibited an increasing trend with age. Finally, regardless of the age groups, participants with 2-3 years of badminton experience had the highest pain rate. These findings might help inform targeted interventions to reduce the high prevalence of pain in various body regions across pre-adolescent and adolescent badminton players.